Investigation of body composition and cardiac sports adaptation in elite water polo players - Zamodics, M.; Babity, M.; Schay, G.; Bucsko-Varga, A.; Kovacs, E.; Horvath, M.; Grebur, K.; Laszlo, M. J.; Fabian, A.; Lakatos, B. K.; Herczeg, S.; Vago, H.; et al. (Sports, 2025)
The effects of physical activity on skeletal muscle mass and cardiac function are well-documented, but there is limited information on the relationship between the two. Furthermore, differentiating between the `athlete`s heart` and pathological cardiac conditions often presents challenges. We aimed to analyze resting echocardiographic parameters in elite water polo athletes, considering sex, anthropometrics, and body composition. We examined 161 youth and adult athletes (age: 19.7 ± 5.6 years, male: 50.9%). Data analysis was performed with R software (version 4.2), using multivariate linear regression models. Confounders besides the main predictor were sex, age, and height. Male players had higher weight (87.55 ± 12.83 vs. 69.77 ± 9.8 kg), height (188.59 ± 6.82 vs. 173.47 ± 6.76 cm), skeletal muscle mass (SMM, 43.87 ± 5.50 vs. 30.38 ± 3.95 kg), and fat-free mass (FFM, 76.60 ± 9.23 vs. 54.52 ± 6.68 kg) and lower percentage of body fat values (12.14 ± 4.00.vs 21.51 ± 4.76%) compared to the female players. Youth players had lower height (178.51 ± 9.53 vs. 186.74 ± 9.27 kg) and weight (74.34 ± 12.12. vs. 88.23 ± 14.66 kg) compared to adults. Left ventricular end-diastolic and end-systolic diameters correlated positively with SMM (Est: 0.38, StE: 0.08, p < 0.001 and Est: 0.42, StE: 0.11, p < 0.001) and FFM (Est: 0.25, StE: 0.05, p < 0.001 and Est: 0.25, StE: 0.06, p < 0.001). Right ventricular end-diastolic diameter correlated positively with SMM (Est: 0.18, StE: 0.08, p < 0.05) and FFM (Est: 0.12, StE: 0.05, p < 0.05). Interventricular septal wall thickness showed positive correlation with SMM (Est: 0.16, StE: 0.04, p < 0.001) and FFM (Est: 0.10, StE: 0.02, p < 0.001). Left ventricular posterior wall thickness correlated with SMM, with a stronger correlation in females (Est: 0.17, StE: 0.05, p < 0.001) than in males (Est:0.7, StE: 0.04, p < 0.05). The close relationship between body composition and cardiac dimensions provides an opportunity for professionals to distinguish between athlete`s heart and pathological conditions.